The Comparative Efficiency of Speech Sound Interventions That Differ by Delivery Modality: Flashcards Versus Tablet. (November 2020) - Werfel, Krystal L.; Brooks, Marren C.; Fitton, Lisa
Although speech–language pathologists increasingly make use of tablets in clinical practice, little research to date has evaluated the effectiveness or efficiency of tablet use for targeting speech sound goals. The twofold purpose of this study was to compare (a) the effectiveness and (b) the efficiency of speech sound intervention using tablets versus flashcards. Four kindergarten students with at least two similar speech sound errors participated in this adapted alternating treatments single subject design study that explored the functional relation between speech sound intervention that differed by modality of delivery (tablet vs. flashcards) and increased speech sound skill in elementary school children with speech sound errors. Flashcards and tablets were both effective single-word speech sound intervention modalities; however, for three of the four participants, flashcards were more efficient than tablets.